Análisis de factibilidad y plan de adopción de la arquitectura tecnológica cloud computing en los procesos de la empresa Agrofar de la ciudad de Mira, provincia del Carchi - Martínez Muñoz, Edison Marcelo (2019)
The adoption of disruptive technological solutions shows an increase in multiple industries such as Health, Education, Retail, Oil, Gas among others; generating economic, environmental, innovation and process efficiency benefits through standardized frameworks. This study focuses on determining the adoption of Cloud Computing in AGROFAR a company in the agricultural inputretail sector in the provinces of Imbabura and Carchi; itself, which takes place in six chapters as follows. Theoretical Framework exposes critical Cloud Computing information such as features, service models, deployment models, risks, success stories, standards, and best practices for adopting and using Gartners TIME tool and other tools. The current status of the services of the company and needs is then determined in Chapter 3 as the starting line for the study. Chapter 4 defines application evaluation criteria based on Business and IT Value indicators with Gartners TIME tool, and shows application categorization in their Reverse, Tolerate, Delete, Migrate quadrants. Consequently, the operational and technical feasibility that validates the feasibility of this study is shown. Finally, an ITIL-based Cloud Computing adoption plan is presented at the Service Transition stage with the main activities to be followed during the adoption processes and the respective conclusions based on the objectives set and the recommendations to help the application of Cloud Computing in the Company AGROFAR.